Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð¿Ñ€ÐµÐ¿Ð°Ñ€Ð°Ñ‚Ð° ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ð½Ð° Ð¼Ð¾Ñ€Ñ„Ð¾Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ðµ ÑÐ²Ð¾Ð¹ÑÑ‚Ð²Ð° ÐºÐ¾Ð¶Ð¸ ÐºÑ€Ñ‹Ñ Ð² ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ðµ in vitro - Purysheva, V. Yu.; Kudokotseva, O. V.; Volina, V. V.; Sokol, L. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The character of influence of the cryopreserved nucleated cells of cord blood on the skin morphology was investigated at different stages of skin culturing in vitro. Under the cord blood influence the period of skin’s viability increased by 15 days as compared with the duration period of control skin viability, the proliferation activities of epidermocytes and dermocytes are stimulated in derma, the fibroblasts number and fibers structures sharply increased. The gland’s structures were increased in derma under the cord blood influence. The cell number was increased in gland’s and in hair follicles in derma when cord blood was added to culturing media.